Impact of storage on the functional characteristics of a fermented cereal product with probiotic potential, containing fruits and phytosterols - Lingua, Mariana Soledad (2021)
The aim of this work was to study the changes in the functional characteristics of a fermented maize product containing fruits, and enriched with phytosterols. Functional characteristics (natural antioxidants and phytosterols content, in vitro antioxidant capacity and probiotic viability), lipid oxidation, and physicochemical parameters were investigated during 4 weeks of storage at 4 °C. The differences between one formulation elaborated with semi-skimmed powdered milk (Basic Product) and another with whey protein isolate (WPI Product) were evaluated. The content of polyphenols, carotenoids and tocopherols remained unchanged during the storage of both formulations. These compounds increased the antioxidant capacity in both products compared to the control formulation (without fruits), which was displayed along the whole storage period. The doses of phytosterols and the probiotic potential were maintained to the end of the storage period for both formulations. Basic and WPI products represent novel foods with desirable functional characteristics preserved during commercial storage. Resumen: El objetivo de este trabajo fue estudiar los cambios en las características funcionales de un producto de maíz fermentado que contiene frutos y está enriquecido con fitoesteroles. Características funcionales (contenido de antioxidantes naturales y fitoesteroles, in vitrocapacidad antioxidante y viabilidad probiótica), oxidación de lípidos y parámetros fisicoquímicos se investigaron durante 4 semanas de almacenamiento a 4 ° C. Se evaluaron las diferencias entre una formulación elaborada con leche en polvo semidesnatada (Producto Básico) y otra con aislado de proteína de suero (Producto WPI). El contenido de polifenoles, carotenoides y tocoferoles se mantuvo sin cambios durante el almacenamiento de ambas formulaciones. Estos compuestos aumentaron la capacidad antioxidante en ambos productos en comparación con la formulación de control (sin frutas), que se mostró durante todo el período de almacenamiento. Las dosis de fitoesteroles y el potencial probiótico se mantuvieron hasta el final del período de almacenamiento para ambas formulaciones. Los productos básicos y WPI representan nuevos alimentos con características funcionales deseables que se conservan durante el almacenamiento comercial.